Language Attitude of the Pakistani Youth towards English, Urdu and Punjabi: A Comparative Study - Furrakh Abbas,Zafar Iqbal (PJDOL, 2023)
The current research aimed at comparing the language attitude of the Pakistani youth towards English, Urdu and Punjabi in a linguistically competitive environment. These languages play significant role in the country and are important in their own way. The objectives of the current research were to explore the integrative and instrumental motivation towards these languages, to analyze the social prestige of these languages and their importance in the global perspective